Changes all the time [compact disc] - Bay, James, 1990-; Bay, James, 1990- (Mercury Records, 2024)
Grammy-nominated singer-songwriter, guitarist and producer James Bay upholds traditions of timeless songcraft and clever lyricism on his fourth studio album, via Mercury Records. The eleven-track project features hit single "Up All Night" with The Lumineers and Noah Kahan, the latter of whom James recently supported on sold-out shows at New York's Madison Square Garden and Boston's Fenway Park.